Nursing training and professional practice: an integrative review of literature - Bianca Joana Mattia; Maria Elisabeth Kleba; Marta Lenise do Prado
ABSTRACT Objective: to identify themes addressed in studies on the repercussions of nursing training in professional practice in Brazil. Method: this is a qualitative research, following the assumptions of Ganong's Integrative Literature Review (1987). The keywords or terms "Health Care" were used; "Nursing"; "Higher Education"; "Teaching in Higher Education"; "Health Service"; "Human Resources" and "Nursing Undergraduates" in consultation with the Virtual Health Library and the CAPES Portal of Journals. Sixty-four studies were found, of which 41 met the inclusion criteria. Results: in the analysis, three themes were highlighted: pedagogical processes and the role of professors and students; curricular structure in nursing education; management of health training. Final considerations: we observed the need to incorporate the Brazilian Unified Health System (SUS) principles and directives in nursing education in the country so that the training is consistent with the needs of professional practice. The study points out to the challenges that emerge with this incorporation.